Physiochemical Evaluation of Selected Local Soilless Substrates for their Effect on Growth and Quality of Lisianthus (Eustoma grandiflora) - Ali, Irslan; Ahmad, Iftikhar; Muhibullah, Fahad; Mujtaba, Ghulam; Majeed, Yasir; Habib, Umer; Ahmad, Mushtaq; Sabahat, Sanjeela (Journal of Agriculture and Veterinary Science, 2024)
Growing substrates are very important for the growth and development of plants, it is quite possible to get maximum yield from flowering crops just by selecting proper growing substrate, a study was conducted to evaluate the physiochemical characteristics and effect of selected local soilless substrates on growth and quality of lisianthus. The experiment was laid out according to Randomized Complete Block Design (RCBD), there were five treatments and every treatment was replicated thrice, each replication was consisting of 20 plants, and were planted in plastic creates of 45×60-inch surface area. Substrates were crushed and well mixed and filled in plastic crates after lining with polythene green net sheet for proper drainage as per following treatments, viz. silt (100%) as control, silt+pressmud (1:1; v/v), silt+coco-coir+pressmud (1:1:1; v/v/v), silt+rice hulls+pressmud (1:1:1; v/v/v), Coco-coir+Rice hulls+press mud (1:1:1; v/v/v). Data collection was done on weekly bases for all the growth and quality parameters. Results indicated that tallest plants (52.0 cm) with higher numbers of leaves (50.0), open flowers per stem (5.4) having thickest stem, bigger size flower (52.8 mm) with higher vase life (12 days) were produced in coco-coir+rice hulls+pressmud (1:1:1; v/v/v) substrate. It is recommended that coco-coir+rice hulls+pressmud (1:1:1; v/v/v) can used for premium quality stem production of lisianthus (Eustoma grandiflora) and would be best local soilless substrate among the tested substrate for commercial production.
Keywords: Specialty cut flowers; Nursery media; Soilless substrates; Seedling production